Is population an asset or a liability to Nigeria's economic growth? Evidence from FM-OLS and ARDL approach to cointegration - Olorunfemi Yasiru Alimi; Akinola Christopher Fagbohun; Mohammed Abubakar (Future Business Journal, 2021)
The controversial debate on whether high population translates to weak or better economic growth has been a topical discussion in the area of development economics. This study therefore uses the data of the Nigerian economy to investigate the links among population growth, growth in output and income per capita growth for the periods of 1981-2018. The study employs both ARDL bound testing approach to cointegration and fully modified least square methods to evaluate the parameter estimates. We found that there exists a long-run relationship between population growth and economic growth in Nigeria. Further, the study found that the statistical and significant effect of population growth is more on long-run income growth than long-run income per capita growth. Meanwhile, in the short-run, an adverse effect is reported from population growth to economic growth, implying that the former has a detrimental effect on the latter. The reason for the adverse effects of population growth in the short-run results from the high number of dependents, whereas, in the long-run, there is a chance of demographic dividend that makes the young people becomes productive in their adulthood. Our findings, therefore, support the league of many studies that population growth is an asset to the long-run economic growth of Nigeria. In contrast, it has a poor impact on economic performance in the short-run. Thus, there is a need for proper and adequate utilization of the country's rising population in appropriate areas of the economy where their efforts would be fully utilized towards improving the overall growth of Nigeria.
Keywords: 650; Economic equality; Government expenditure; Income; Investment; Population growth